2022
DOI: 10.1093/ajcn/nqab337
|View full text |Cite
|
Sign up to set email alerts
|

Fermentable oligo-, di-, monosaccharides, and polyols (FODMAPs), but not gluten, elicit modest symptoms of irritable bowel syndrome: a double-blind, placebo-controlled, randomized three-way crossover trial

Abstract: Background Irritable bowel syndrome (IBS) has been associated with diets rich in fermentable oligo-, di-, monosaccharides and polyols (FODMAPs), and gluten. Most previous studies have been single-blind and have focused on elimination of FODMAPs or provocation with single FODMAPs. The effect of gluten is unclear, large trials isolating the effect of gluten from that of FODMAPs are needed. Objective The aims of this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 43 publications
3
32
0
3
Order By: Relevance
“…Data and samples were obtained from a double-blind, placebo-controlled, randomized 3-way crossover trial conducted in 2018–2019, comprising 110 people with IBS. In total, 103 people completed the trial (20): 90 women and 13 men, 46 ± 15 years of age, with a BMI 24 ± 4 kg/m 2 . All participants had severe to moderate IBS, diagnosed by a gastroenterologist according to the Rome IV criteria (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data and samples were obtained from a double-blind, placebo-controlled, randomized 3-way crossover trial conducted in 2018–2019, comprising 110 people with IBS. In total, 103 people completed the trial (20): 90 women and 13 men, 46 ± 15 years of age, with a BMI 24 ± 4 kg/m 2 . All participants had severe to moderate IBS, diagnosed by a gastroenterologist according to the Rome IV criteria (1).…”
Section: Methodsmentioning
confidence: 99%
“…The trial was approved by the Ethics Review Board, Uppsala (2018/ 159), and registered at www.clinicaltrials.gov as NCT03653689. The study is described in detail elsewhere (20).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…This study demonstrated significantly higher Gastrointestinal Symptom Rating Scale (GSRS) scores for individuals consuming fructans rather than gluten (p = 0.049) [28]. In addition, a recent double-blind placebo RCT in 110 patients with IBS demonstrated that consumption of FODMAPs led to modest increases in IBS-SSS compared to the consumption of gluten (240 vs 208, p = 0.013) [29]. However, a recent study in patients with IBS showed no correlation of GI symptoms with fructan intake [30].…”
Section: Gluten-free Dietmentioning
confidence: 72%
“…Interestingly, the clinical response to a low FODMAP diet may be predicted by gut microbiota composition before the start of the dietary intervention (Bennet et al, 2018; Valdez-Palomares et al, 2021; Valeur et al, 2018), by high colonic methane and SCFA production (Eetemadi and Tagkopoulos, 2021), and by high saccharolytic fermentation activity (Zhang et al, 2021), supporting the importance of the gut microenvironment. However, not all studies have demonstrated a correlation between fermentation or gut microbiota profile and IBS symptoms (Table 4) or show substantial benefits in symptomatology (Nordin et al, 2022). In addition, even though a low FODMAP diet or β-GOS supplementation for 4 weeks have very similar effects on symptom improvement, discontinuation of a low FODMAP diet may lead to a faster reappearance of symptoms as compared to elimination of prebiotic β-GOS supplementation.…”
Section: Food and Dietary Habitsmentioning
confidence: 99%
“…This entity is known as non-coeliac gluten/wheat intolerance and can overlap with IBS (Spencer et al, 2014). The exclusion of gluten from the diet has been shown to successfully improve IBS symptoms in subgroups of patients (Supplementary References: Gluten-free diet), but not all studies agree with this (Nordin et al, 2022). Interestingly, one study demonstrated that approximately one third of IBS patients who benefit from a gluten-free diet suffer from wheat sensitivity (Barmeyer et al, 2017), which may be triggered by high levels of the FODMAP fructan found in wheat (Spencer et al, 2014).…”
Section: Low Fodmap Dietmentioning
confidence: 99%